Sport and Social Entrepreneurship in Sweden (Springer International Publishing, 2018)
This edited collection explores the concept of social entrepreneurship in sport, examining how it has been used in Swedish society to date. It explores how this approach in sport could also be used to address wider socio-political issues, including economic, political, cultural and pedagogical in European society. Sport and Social Entrepreneurship in Sweden explores different social entrepreneurship projects which have created new forms of activity and reached groups of children and young people previously disengaged in sport. The authors also highlight the growing momentum of this kind of entrepreneurship in Sweden after a period of societal upheaval that has resulted in a blurring of social borders and the founding of new organisational forms. This book contributes to the formation of a new field of research, involving theoretical and empirical work on the characteristics and possibilities of social entrepreneurship in relation to sport. .